Behavioral choice of manufacturers, recyclers and customers in Trade-In Programs. - Chan He; Qianru An (PLoS ONE)
This study investigates the behavioral choices of manufacturers, recyclers, and customers in Trade-In Programs designed to promote recycling and environmental sustainability. Using a manufacturer-led evolutionary game model, the research explores how factors such as government policies, market demand, financial incentives, and the simplicity of participation impact stakeholder engagement in these programs. Numerical simulations were conducted to analyze the effects of specific parameters on each participants' willingness to participate. Results show that increased subsidies and investment in innovation by manufacturers significantly enhance recycler and customer participation in ethic Trade-In Programs. Conversely, higher revenue-sharing by manufacturers tends to reduce engagement from both parties, while manufacturers receiving substantial brand and social benefits alongside government subsidies to encourage broader stakeholder involvement. These findings offer critical insights for designing effective Trade-In Programs, supporting sustainable recycling practices and circular economy principles. The study provides actionable guidance for policymakers and industry leaders aiming to boost participation in environmentally focused recycling initiatives, laying a foundation for more sustainable industrial practices.